2022
DOI: 10.1002/jsfa.11959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mulberry leaf polysaccharides on the baking and staling properties of frozen dough bread

Abstract: BACKGROUND Deterioration in frozen dough bread easily occurs in store, resulting in tremendous economic waste. Therefore, it is imperative to find natural additives to improve storage staling. The effects of mulberry leaf polysaccharides (MLP) were studied in terms of baking, retrogradation and microstructural aspects in frozen dough bread. RESULTS The incorporation of MLP improved the specific volume and reduced the hardness of bread during room storage, with 1% MLP showing the best results. The results of X‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Also, according to Xie et al ., hydrophilic gum could improve the specific volume by retaining the ability of the gluten starch complex. TSP has hydrophilic properties and helps maintain the strength of the gluten net and promote the uniformity of pores 46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, according to Xie et al ., hydrophilic gum could improve the specific volume by retaining the ability of the gluten starch complex. TSP has hydrophilic properties and helps maintain the strength of the gluten net and promote the uniformity of pores 46 …”
Section: Resultsmentioning
confidence: 99%
“…TSP has hydrophilic properties and helps maintain the strength of the gluten net and promote the uniformity of pores. 46…”
Section: Rheological Analysis Of Frozen Doughmentioning
confidence: 99%
“…Frozen dough bread is prone to being stale and wasteful in shops. Xie 105 measured the specific volume, hardness, aging kinetics, and moisture content by using MLPs as natural additives and observed that MLPs reduced the storage kinetics of the storage process, retarded water migration and decreased bread water loss, which was credited with the hydroxyl structure of mulberry polysaccharides that can compete with that of bread. This is because the hydroxyl structure of mulberry leaf polysaccharides competes with the starch in bread for bound water, slowing down the undesirable phenomenon of structural hardening during storage.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Each sample was repeated 3 times. The hardness under different storage periods were fitted to the 'Avrami model' to calculate the staling rates of samples following the research method [6], and the Avrami equation was as follows:…”
Section: Hardness Analysis and Staling Kineticsmentioning
confidence: 99%
“…Meanwhile, amylopectin molecules in the expanded starch granules bind to each other, resulting in increased rolls hardness and staling. The uniformity and stability of the microstructure of rolls will also be affected by these interactions, thus affecting the quality of the rolls [6].…”
Section: Introductionmentioning
confidence: 99%